Health services availability and readiness in seven provinces of Nepal: further analysis of the 2015 Nepal Health Facility Survey: dhs futher analysis reports No. 115. - Aryal, Krishna Kumar (2018)
SUMMARY: The overall objective of this report is to provide health care delivery system program managers with information on the level of availability of basic and essential services in health facilities and the extent of preparedness of the facilities to provide quality health services in each of the seven provinces of Nepal. Following release of the report of the 2015 Nepal Health Facility Survey, the Ministry of Health and Population identified the need to disaggregate the survey results at the province level to allow policymakers to better determine how best to allocate available resources among the provinces. This report is intended to help fill this objective. We performed further analysis of 2015 NHFS dataset, which included data from the following: an inventory questionnaire for all 963 facilities visited; interviews of 4,057 service providers; interviews of 987 Health Facility Operation Management Committee (HFOMC) and Hospital Development Committee (HDC) members; 2,186 sick child care observations; 1,509 antenatal care (ANC) client observations; 772 family planning client observations; and exit interviews with the caretakers of the sick children and with ANC clients, family planning clients, and 309 postpartum mothers. The report shows descriptive results for seven provinces of Nepal. In addition, we carried out multivariate analyses for five outcome variables of interest: provision of quality ANC services; provision of quality family planning services; provision of quality IMNCI services; and availability of basic diagnostic tests and safe disposal of health care waste. Regarding general service readiness and quality of care, we found that availability of basic client services is not universal across provinces, especially STI services, which ranged from 63% to 82%. Availability of laboratory services ranged widely, from 32% in Province 7 to just 3% in Province 4, but Province 4 had the highest proportion of facilities meeting minimum standards of quality of care on all nine items, at 3% compared with the national average of about 1%. The percentage of facilities where clients reported having received all four specified ANC services was quite low, ranging from a high of 11% of clients in Province 5 to 2% in Province 3. Multivariate analysis showed that Province 5 had four and a half times higher odds of providing quality ANC services compared with Province 4, the reference. All provinces except Province 6 had statistically significant higher odds of providing quality family planning services. Provinces 3 and 6 had statistically significant higher odds of providing quality IMNCI services compared with Province 7, the reference. Province 6 had higher odds of disposing health care waste safely compared with Province 4, the reference. Regarding child health care, 85% of health facilities offered all three basic services (outpatient curative care for sick children, growth monitoring, and child vaccination), with a range among provinces from 77% (Province 2) to 91% (Province 4). Key essential antibiotics such as amoxicillin and cotrimoxazole were much less readily available. More than 96% of the facilities in each of the seven provinces offered at least one modern method of temporary family planning, while the proportion of facilities offering male or female sterilization ranged from 23% (Province 4) to 53% (Province 6). In at least 89% of facilities every contraceptive method provided by the facility was available on the day of the survey in each of the seven provinces, with the highest proportion in Province 4, at 100%. Regarding ANC, delivery, and newborn care services, at least 94% of facilities offered ANC services across all provinces. Nearly half of facilities nationwide provided normal vaginal delivery services, ranging from 23% of facilities in Province 2 to 83% in Province 6. The proportion of facilities providing medical abortion ranged from 13% in Province 7 to 42% in Province 2. The proportion of facilities with all essential medicines for newborns (tetracycline eye ointment, 4% chlorhexidine gel, injectable gentamicin, ceftriaxone powder for injection, and amoxicillin suspension or dispersible pediatric dosed tablet) was less than 2% across all provinces. Concerning services related to HIV/AIDS and sexually transmitted infections (STIs), 6% of facilities had an HIV testing system, either in the facility or through an external testing site, from 3% of facilities in Province 1 and 6 to 9% of facilities in Province 3. Among the facilities with an HIV testing system, the proportion with HIV testing capacity at the facility ranged from 73% (Province 2) to 94% (Province 5). In relation to non-communicable diseases, the proportion of facilities diagnosing, prescribing treatment, and/or managing patients with diabetes ranged from 15% (Province 2) to 25% (Province 3). The percentage of facilities nationwide that reported offering services for cardiovascular diseases was over 73%, from 64% in Province 6 to 84% in Province 7. We found that 94% of facilities nationwide diagnose, prescribe treatment for, or manage patients with chronic respiratory diseases, with a range from 80% in Province 6 to 97% in Province 7. Among all facilities, the proportion offering malaria diagnosis and treatment services ranged from 30% in Province 6 to 75% in Province 2. Over 90% of facilities across all provinces reported that they provide TB diagnostic or treatment and/or treatment follow-up services. In summary, major gaps among provinces exist in diagnostic service availability in health posts; availability of key essential medicines for child health services; and ANC service readiness in terms of availability of guidelines, equipment, and essential medicines. There is also a considerable gap among the provinces in the quality of ANC, family planning, and IMNCI services. Availability of basic diagnostic tests varied by type of facility, with public and private level hospitals having higher odds of availability after adjusting for covariates. The way forward would be to focus on improving service availability and readiness in the lowest performing provinces and to keep up the standards in high performing provinces. ummary of Results of NHSS RF Indicators NHSS RF Indicators Provinces National Average Province 1 Province 2 Province 3 Province 4 Province 5 Province 6 Province 7 1 Availability of tracer medicines (NHSS RF: OC1.4) 0.6 0.1 0.7 0.5 1.0 0.6 2.5 0.8 2 Sanctioned posts filled (NHSS RF: OP1b1.1) (All providers) 69.8 73.6 65.9 78.1 73.7 68.1 74.4 71.3 3 Timely supply of family planning commodities (NHSS RF: OP1c2.1) 82.1 72.4 85.7 84.4 75 97.8 77.3 81.7 4 Storage practice for medicines (NHSS RF: OP1c2.2) (all storage criteria met 68.3 55.2 64.4 63.3 69 57.9 71.6 64.1 5 Health facilities meeting minimum standards of quality of care at point of delivery (NHSS RF: OC2.1) 0.0 0.0 0.8 3.2 0.3 0.3 0.2 0.7 6a Provision of quality ANC services as per national standards (NHSS RF: OC2.2) 5.7 5.0 2.3 5.3 10.5 6.7 7.3 5.3 6b Provision of quality family planning services as per national standards (NHSS RF: OC2.2) 9.0 8.5 8.1 1.3 12.3 4.9 27.5 9.9 6c Provision of quality IMNCI services as per national standards (NHSS RF: OC2.2) 20.4 22.3 23.7 29.5 26.1 33.7 20.3 24 7a Compliance with service delivery protocols/guidelines for ANC services (NHSS RF: OP2.1.1) 0.5 0.0 0.3 0.2 0.0 0.0 0.2 0.2 7b Compliance with service delivery protocols/guidelines for family planning services (NHSS RF: OP2.1.1) 0.3 0.1 2.3 0.2 1.1 0.3 0.5 0.8 7c Compliance with service delivery protocols/guidelines for IMNCI services (NHSS RF: OP2.1.1) 0.3 0.6 0.2 3.2 1.9 0.0 0.2 0.9 8 Laboratory diagnostic capacity - basic test (NHSS RF: OP2.1.3) (All basic tests - PHCCs and hospitals only included) 3.4 22.2 12.8 8.7 13.3 18.2 16.3 12.6 9 Segregation of waste (NHSS RF: OP2.3.1) 90.4 82.4 93.5 85.5 87.9 68.4 79.9 85.9 10 Safe disposal of health care waste (NHSS RF: OP2.3.2) (both sharps and medical waste) 81.9 74.0 82.3 63.9 80.6 81.6 74.8 77.4 11 Clients receiving free health care (NHSS RF: OC3.1) 83.7 95.3 70.4 86.4 92.3 77.0 87.6 85.9 12 Availability of basic client services (NHSS RF: OP3.1.1) 63.2 53.8 68.9 65.5 63.1 52.3 62.9 62 13 Comprehensive emergency obstetric and newborn care (CEmONC) sites (NHSS RF: OP3.1.3) 50.0 25.0 53.8 18.2 50.0 20.0 44.4 39.0 14 Health Posts with laboratory services (NHSS RF: OP5.1.2) 12.3 19 11.4 2.7 11.3 5.4 31.9 13.4